Perbandingan return saham dengan indikator bollinger band dan stochastic oscillator pada perusahaan sub sektor telekomunikasi, bank dan batu bara - Ismail Husaini; Masfar Gazali (University of Merdeka Malang, 2023)
This study aims to compare the level of return and make decisions at the right time to sell and buy shares in the Telecommunications, Banks and Coal Sub-Sector Companies registered in the LQ45 index. Technical indicators used are Bollinger Band and Stochastic. The data used are secondary data, with samples of shares of Telecommunications, Banks and Coal Sub-Sector Companies registered in the LQ45 index period September 2020 - September 2021. Sampling is carried out with purposive sampling technique. Data retrieval Using TradingView Software on the TradingView.com website. Based on the results of research from Bollinger Band and Stochastic indicators. What produces greater profits is to use the Stochastic Oscillator. With moments, the purchase signal will appear when the K% line cuts the D% line from the top up in the Oversold zone which is confirmed by cutting the stochastic line to the vertical scale of 20, this situation is called Golden Cross (buy moment) on the grounds that the price will soon be ride. Meanwhile, the selling signal will appear when the K% line cuts the D% line from top to bottom in the overbought zone which is confirmed by cutting the stochastic line to the vertical scale 80, this situation is called Death Cross (sell moment) on the grounds that the price will soon come down